Expression patterns of anoctamin 1 and anoctamin 2 chloride channels in the mammalian nose - Dauner, Kristin; Lißmann, Judith; Jeridi, Semir; Frings, Stephan; Möhrlen, Frank (Cell & tissue research, 2012)
Calcium-activated chloride channels are expressed in chemosensory neurons of the nose and contribute to secretory processes and sensory signal transduction. These channels are thought to be members of
Gesehen am 14.02.2017